Development of Selenized Lactic Acid Bacteria and their Selenium Bioaccummulation Capacity - Gabriela Krausova; Antonin Kana; Ivana Hyrslova; Iva Mrvikova; Miloslava Kavkova (Fermentation, 2020)
Selenized lactic acid bacteria (LAB) represent potentially safe and effective sources of selenium (Se), essential for human health, as lactic acid fermentation improves Se bioavailability and reduces its toxicity. LAB are generally recognized as safe (GRAS) and widely used in fermented dairy products. To facilitate selenized LAB implementation as a functional food, we developed and characterized new Se-enriched strains based on the food industry commercial strains Streptococcus thermophilus CCDM 144 and Enterococcus faecium CCDM 922A as representatives of two LAB genera. We evaluated Se bioaccumulation capacity, Se biotransformation and growth ability in the presence of different sodium selenite concentrations (0–50 mg/L), and antioxidant properties (2, 2-diphenyl-1-picrylhydrazyl (DPPH) method) and cell surface hydrophobicity between Se-enriched and parental strains in vitro. Sodium selenite addition did not negatively influence growth of either strain; thus, 50 mg/L was chosen as the optimal concentration based on strain accumulation capacity. Selenization improved the antioxidant properties of both strains and significantly increased their cell surface hydrophobicity (p < 0.05). To our knowledge, this represents the first report of Se-enriched strain hydrophobicity as well as the first on Se speciation in families Enterococcaceae and Streptococcaceae. Moreover, both tested strains demonstrated good potential for Se-enrichment, providing a foundation for further in vitro and in vivo studies to confirm the suitability of these Se-enriched strains for industrial applications.